8-Hydroxylation and Glucuronidation of Mirtazapine in Japanese Psychiatric Patients: Significance of the Glucuronidation Pathway of 8-Hydroxy-Mirtazapine - Shinozaki, Masataka; Pierce, Jason; Hayashi, Yuki; Watanabe, Takashi; Sasaki, Taro; Komahashi-Sasaki, Hazuki; Akiyama, Kazufumi; Kato, Kazuko; Inoue, Yoshimasa; Tsuchimine, Shoko; Yasui-Furukori, Norio; Ozeki, Yuji; Shimoda, Kazutaka (Pharmacopsychiatry, 2019)
Introduction  To investigate the metabolism of mirtazapine (MIR) in Japanese psychiatric patients, we determined the plasma levels of MIR, N-desmethylmirtazapine (DMIR), 8-hydroxy-mirtazapine (8-OH-MIR), mirtazapine glucuronide (MIR-G), and 8-hydroxy-mirtazapine glucuronide (8-OH-MIR-G).Methods  Seventy-nine Japanese psychiatric patients were treated with MIR for 1–8 weeks to achieve a steady-state concentration. Plasma levels of MIR, DMIR, and 8-OH-MIR were determined using high-performance liquid chromatography. Plasma concentrations of MIR-G and 8-OH-MIR-G were determined by total MIR and total 8-OH-MIR (i. e., concentrations after hydrolysis) minus unconjugated MIR and unconjugated 8-OH-MIR, respectively. Polymerase chain reaction was used to determine CYP2D6 genotypes.Results  Plasma levels of 8-OH-MIR were lower than those of MIR and DMIR (median 1.42 nmol/L vs. 92.71 nmol/L and 44.96 nmol/L, respectively). The plasma levels (median) of MIR-G and 8-OH-MIR-G were 75.00 nmol/L and 111.60 nmol/L, giving MIR-G/MIR and 8-OH-MIR-G/8-OH-MIR ratios of 0.92 and 59.50, respectively. Multiple regression analysis revealed that smoking was correlated with the plasma MIR concentration (dose- and body weight–corrected, p=0.040) and that age (years) was significantly correlated with the plasma DMIR concentration (dose- and body weight–corrected, p=0.018). The steady-state plasma concentrations of MIR and its metabolites were unaffected by the number of CYP2D6*5 and CYP2D6*10 alleles.Discussion  The plasma concentration of 8-OH-MIR was as low as 1.42 nmol/L, whereas 8-OH-MIR-G had an approximate 59.50 times higher concentration than 8-OH-MIR, suggesting a significant role for hydroxylation of MIR and its glucuronidation in the Japanese population.
Keywords: mirtazapine; hydroxylation; glucuronidation; pharmacokinetics; pharmacogenetics